Two-Stage Amplification of Receptors Using a Multilevel Orthogonal/Simultaneous Dynamic Combinatorial Library - Escalante, Andrea Marta (2012)
Sequential activation of different reversible exchange reactions in a dynamic combinatorial library allows directed exploration of the chemical space: initially a macrocyclic scaffold is selected by the template and finally side chain and conformational constrains are introduced into such a scaffold.